Pelatihan penyusunan laporan keuangan UMKM di Kabupaten Kampar - Nur Azlina; Taufeni Taufik; Sri Melisa Putri; M. Haykal Daditullah Indrapraja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This community service activity aims to 1) provide an understanding of accounting for MSME managers in order to improve MSME financial performance, 2) Improve skills in compiling financial reports according to SAK EMKM. The method used in community service activities is to use training methods for several MSME managers in Kampar Regency for selected UMKM. Regarding the procedures for preparing financial reports by visiting the target MSMEs one by one while continuing to implement the Covid-19 protocol. Community Service activities are carried out in September 2020, which starts at 08.00 WIB - finished. With this training, MSME managers can understand accounting and can prepare financial reports in accordance with Indonesian SAK EMKM. With the existence of financial reports prepared according to standards, it will be able to provide complete financial information for MSME managers, besides that it can also be used by managers as one of the requirements when they want to apply for a loan.